Improving The Quality of Service Through The Utilization of Information Technology in Supporting The Sales Performance of Subsidied Fertilizer - Milearosari, Agnes Tiffani; Ramadhan, Hanifa Maulani (Profit: Jurnal Adminsitrasi Bisnis, 2023)
PT Pupuk Indonesia (Persero) is a State-Owned Enterprise (BUMN) which is engaged in the agrochemical industry. PT Pupuk Indonesia (Persero) is committed to maintaining the smooth distribution of subsidized fertilizers and improving service to customers through the 6T principles: Right Time, Right Price, Right Type, Right Amount, Right Place and Right Quality. The purposes of this study are (1) to determine the services provided by PT Pupuk Indonesia (Persero) in the process of selling Subsidized Fertilizers, (2) to determine the implementation of internal service quality and information technology in improving service quality at PT Pupuk Indonesia (Persero), ( 3) to determine the effectiveness of the implementation of internal service quality and information technology in supporting the sales performance of subsidized fertilizers at PT Pupuk Indonesia (Persero). This study uses descriptive qualitative methods with data collection through interviews, observation, and documentation. The result of this research is that PT Pupuk Indonesia always tries to carry out assignments from the government, so that the application of the 6T principle can run properly. PT Pupuk Indonesia has implemented the internal service component well through the application of information technology to help services in the distribution of subsidized fertilizers become more effective.